Image strategies of Ukraine: media linguistic discourse - Плясун, Ольга Миколаївна (Київський національний університет імені Тараса Шевченка, 2019)
Globalization processes of the information era, mediatization of modern society make it possible to apply to image new methods of analysis. Since today’s state image is formed in media space, media linguistic area of image research seems to be one of the most promising. The relevant problem is connected with formation of effective image strategies, which we define as complex image actions, tactics, technologies etc. aimed at creating a successful image. The article analyzes innovative scientific investigations on image issues of leading world (A. Cheddad, J. Condell, K. Curranand, P. McKevitt, P. Diaz Rodriguez) and Ukrainian (H. Shevchenko, I. Kysarets, I. Lysychkina, O. Dobrozhanska, V. Fedorova) linguists. The author focuses on media discourse of image studies (works by V. Chekalyuk, I. Valevska etc.). It is postulated that media linguistic aspect of imageology is only developing and is considered mainly in the context of suggestive linguistics. The image potential of emotional-evaluative constructions, therapeutic metaphors / texts, reclamation lexems, verbalizers with positive semantics etc is determined. According to the author’s argumentation, such language formulas have strong suggestive properties. The linguistic component of state image strategies implementation is analyzed. The author states that in Ukrainian media space the strategies of positive self-presentation, highlighting uniqueness and appealing to values can be quite effective. The scholar studies the linguistic resource of image publications about Ukraine on official government pages in social networks (Facebook and Twitter). The author systematically proves that image strategies in modern communication achieve maximum effect when verbal communication is accompanied by visualization of image symbols, situations and associations. Thus, an effective image mark is created, where there is a sublimation of meaning and expression, which can be considered a certain suggestive ideal in modern media.

Глобалізаційні процеси інформаційної ери, медіатизація суспільства уможливлюють застосування до іміджу нових методів аналізу. Оскільки сьогодні державний імідж формується, зокрема, і в засобах масової інформації, одним із найбільш перспективних напрямів іміджевих досліджень є медіалінгвістичний, у межах якого актуальним залишається питання формування ефективних іміджевих стратегій – комплексу іміджевих дій, тактик, прийомів, технологій, спрямованих на створення успішного іміджу.  У статті аналізуються інноваційні наукові розвідки з іміджевої проблематики провідних світових (А. Чеддад, Д. Конделл, К. Керран, П. Мак Кевітт, П. Діас Родрігес та ін.) й українських (Г. Шевченко, І. Кисарець, І. Лисичкіна, О. Доброжанська, В. Федорова) учених-лінгвістів, аргументується перспектива медійного дискурсу іміджевих досліджень (роботи В. Чекалюк, І. Валевської та ін.). Постулюється теза про зародження в сучасній науці медіалінгвістичного аспекту іміджелогії, який розглядається переважно в колі питань мовознавчого ресурсу сугестії. Визначається іміджевий потенціал специфічних мовних формул, що мають сугестивну властивість, зокрема, емоційно-оцінних конструкцій, терапевтичних метафор/текстів, меліоративних лексем, вербалізаторів із позитивною семантикою та ін. Аналізується лінгвістичний компонент імплементації державних іміджевих стратегій, з-поміж яких найбільш ефективними для України є стратегія позитивної самопрезентації, стратегія підкреслення власної унікальності, стратегія апеляції до цінностей та ін. Досліджується й фахово інтерпретується мовний ресурс іміджевих публікацій про Україну на офіційних урядових сторінках у соціальних мережах (Facebook, Twitter). Автор планомірно доводить, що в сучасній комунікації іміджеві стратегії досягають максимального ефекту саме тоді, коли вони супроводжуються візуалізацією іміджевих символів, ситуацій та асоціацій. Таким чином, створюється ефективний іміджевий знак, в якому сублімуються смисл і експресія, що і є певним сугестивним ідеалом в сучасних медіа.
Іміджеві стратегії України: медіалінгвістичний дискурс
Keywords: linguistic imageology; image; linguistic means of image formation; image strategies of Ukraine; media.; лінгвоіміджелогія; імідж; лінгвістичні засоби конструювання іміджу; іміджеві стратегії України; медіа.